2008
DOI: 10.1158/1055-9965.epi-08-0261
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression Profiles Define Pathways in Colorectal Cancer Cell Lines Affected by Celecoxib

Abstract: It is well established that celecoxib, a selective inhibitor of cyclooxygenase-2 (COX-2) and a tested chemopreventive agent, has several COX-2 -independent activities. In an attempt to better understand COX-2 -independent molecular mechanisms underlying the chemopreventive activity of celecoxib, we did global transcription profiling of celecoxib-treated COX-2 -positive and COX-2 -deficient colorectal cancer cell lines. Celecoxib treatment resulted in significantly altered expression levels of over 1,000 to 3,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Microarray analysis of the colorectal cancer cell line HT-29 treated with 1mM and 5mM aspirin showed an up-regulation of GADD45α (Yin et al, 2006). Further to this, microarray analysis also shows GADD45 gene expression to be upregulated by NS-398 (Huang et al, 2006) and celecoxib (Fatima et al, 2008) in colorectal cancer cells and by ibuprofen in human gastric adenocarcinoma cell line (Bonelli et al, 2010). Suppression of GADD45α expression confers resistance to sulindac and indomethacin induced gastric mucosal injury and apoptosis (Chiou et al, 2010) .…”
Section: Nsaids and Dna Repair Protein Expressionmentioning
confidence: 75%
See 2 more Smart Citations
“…Microarray analysis of the colorectal cancer cell line HT-29 treated with 1mM and 5mM aspirin showed an up-regulation of GADD45α (Yin et al, 2006). Further to this, microarray analysis also shows GADD45 gene expression to be upregulated by NS-398 (Huang et al, 2006) and celecoxib (Fatima et al, 2008) in colorectal cancer cells and by ibuprofen in human gastric adenocarcinoma cell line (Bonelli et al, 2010). Suppression of GADD45α expression confers resistance to sulindac and indomethacin induced gastric mucosal injury and apoptosis (Chiou et al, 2010) .…”
Section: Nsaids and Dna Repair Protein Expressionmentioning
confidence: 75%
“…PCNA gene expression has been shown to be up-regulated by ibuprofen treatment of a human gastric adenocarcinoma cell line (Bonelli et al, 2010), and also in the human hepatocellular carcinoma cell line HepG2 treated with 25mM vanillin (Cheng et al, 2007). In contrast, down-regulation of PCNA gene expression has been reported in colorectal cancer cell lines treated with celecoxib suggesting that these compounds may modulate cell cycle regulation in these model (Fatima et al, 2008). Interestingly, FADD gene expression is down-regulated by NS-398 but upregulated by indomethacin in the colorectal cancer cell line Caco-2 (Huang et al, 2006).…”
Section: Nsaids and Dna Repair Protein Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data indicated that there is an induction of pro-apoptotic response (Bax and Bid) in a dose-time-dependent manner. Global transcription proiling in colon cancers implied modulations on the genes related to cell cycle and apoptosis, but these changes were mostly observed in both COX-2 (+) and (-) cell lines [33]. Celecoxib induces cell cycle arrest at G1-phase, together with decreases in the inhibition of various cyclin expressions.…”
Section: Molecular Pathway Studies On Coxibsmentioning
confidence: 99%
“…We have shown that the cyclooxygenase-2 (COX-2) inhibitor celecoxib (Celebrex) inhibits the development of pulmonary metastases without affecting growth of the primary tumor in a murine mode of ES [6,7]. The antitumor effects of COX-2 inhibitors, particularly celecoxib, have been the subject of intensive research in recent years [8][9][10][11], but the mechanism of celecoxib's antineoplastic effect has not been clearly elucidated.…”
mentioning
confidence: 99%